2018
DOI: 10.1103/physrevb.98.245420
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected thermal conductivity enhancement in pillared graphene nanoribbon with isotopic resonance

Abstract: Thermal transport in nanoribbon based nanostructures is critical to advancing its applications. Wave effects of phonons can give rise to controllability of heat conduction in nanostructures beyond that by particle scattering. In this paper, by introducing structural resonance, we systematically studied the thermal conductivity of graphene nanoribbon based phononic metamaterials (GNPM) through non-equilibrium molecular dynamical simulation. Interestingly, it is found that the thermal conductivity of GNPM is cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 62 publications
5
66
0
Order By: Relevance
“…Different type of MoS2NT is constructed by rolling up SLMoS2 based on specific lattice vector r = ma1 + na2, where the lattice constants of the primitive cell are a1= a2=3.147 Å (as shown in figure 1a). Noting that our study only focuses on armchair nanotube (aNT, m=n) and zigzag nanotube (zNT, The classical non-equilibrium molecular dynamics (NEMD) method has been employed in the calculation of thermal properties [12][13][14][15][16][17]. The thermal conductivity is calculated based on the Fourier's law of heat conduction as…”
Section: Model and Methodsmentioning
confidence: 99%
“…Different type of MoS2NT is constructed by rolling up SLMoS2 based on specific lattice vector r = ma1 + na2, where the lattice constants of the primitive cell are a1= a2=3.147 Å (as shown in figure 1a). Noting that our study only focuses on armchair nanotube (aNT, m=n) and zigzag nanotube (zNT, The classical non-equilibrium molecular dynamics (NEMD) method has been employed in the calculation of thermal properties [12][13][14][15][16][17]. The thermal conductivity is calculated based on the Fourier's law of heat conduction as…”
Section: Model and Methodsmentioning
confidence: 99%
“…higher average temperature in the PnC defect, which additionally leads to an increased thermal response. It should, however, be mentioned that the localized temperature is not a result of phonon localization due to the PnC as has been reported in previous investigations [23,24]. Given the huge differences in the wavelengths of heat-transporting phonons (on the order of nanometers) and the lattice constants used here (≥ 30 μm), the PnC cannot control the heat flow coherently.…”
Section: Introductionmentioning
confidence: 57%
“…Subsequent studies also confirmed this conclusion (Liu et al, 2018b;Nomura et al, 2018). Apart from silicon-based nanostrucutres, (Ma et al, 2018) reported a reduction of half thermal conductivity in nanopillared GNRs compared to pristine nanoribbons. It was also found that isotopic doping in nanopillars is conducive to phonon transport, because doping could weaken the hybridization degree.…”
Section: From the Perspective Of Phonon-wave Picturementioning
confidence: 71%